Comparison of Clinic - Histopathologic Findings and Morphometric Measurements of Subclinical Laminitic Claws in Dairy Cattle - Göksen Çeçen Ayalp; Ülke Gülsüm Çalışkan; Aylin Alasonyalılar Demirer (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to evaluate the clinic-histopathologic characteristics and to compare the morphometric measurements of healthy and subclinical laminitic claws of dairy cattle at different ages and weights. Non-lame 60 Holstein feet randomly collected from the slaughterhouse were evaluated. The effects of age, body-weight, claw location (right front lateal or right front medial etc), and presence of laminitis were investigated. The claws’ conformation were evaluated morphometrically with ten measurements (toe length, toe height, outer and inner edges of the claw, heel height, the length of heel, the length of diagonal front wall, dorsal hoof angle, the width and the length of the sole). The claws were classified as normal or laminitic according to the histopathologic findings. The clinical findings of laminitis was confirmed on 71.2% of the claws (n=66). The toe length, toe height, the height of outer and inner edges of the claw, heel height, the length of heel, the length of diagonal front wall were smaller in laminitic claws. The dorsal hoof angle of healthy claws were bigger and statistically significant than the laminitic claws. Small haemorrhagic areas were determined in the parietal corium in the laminitic claws comparing to macroscopically healthy claws. The histopathologic characteristics of the corium of laminitic claws involve the hyperaemia, haemorrhages, oedema, thrombosis of capillaries and presence of mononuclear cell infiltration in dermis, stretching epidermal lamella, necrosis of epithelial cells and detachment of the lamellar basement membrane. According to this study results, contrary to literature, there was not a reliable relation between some changes in morphological structure of the claws and the presence of the laminitis were observed.